Improving the Quality of Financial Reporting Through the Implementation of Microsoft Excel for SMEs in Parung Serab, Tangerang - Riyani, Etik Ipda; Tantri, Sakina Nusarifa; Hardiana, Nadhira; Widiastuti, Yeni; Muktiyanto, Ali; Agustin, Fira (International Journal of Community Service Learning, 2024)
Bookkeeping is one of the activities in financial management in Micro, Small, and Medium Enterprises (MSMEs) as an effort to improve the quality of financial reporting. The low quality of MSME financial reporting impacts other problems, such as reduced productivity and constraints on other MSME business processes. MSMEs experience this in Parung Serab Village, Tangerang. Parung Serab MSMEs experienced a decline in productivity due to a need for more consistency in reporting and financial management. Moreover, due to inconsistent financial management, MSMEs cannot open up and improve their finances, resulting in losses. Due to this problem, the team serves the community by assisting in simple bookkeeping using Microsoft Excel tools. This community service activity aims to improve the quality of MSME financial reporting through simple bookkeeping using a mentoring approach. This qualitative study uses data about the problems faced by MSMEs collected through an interview process. The subjects of this assistance are 15 MSMEs in Parung Serab, Ciledug. The result of this assistance is that with simple bookkeeping using Microsoft Excel format, MSMEs in Parung Serab have succeeded in maintaining consistency in financial management and reporting. This assistance means that by maintaining consistency in financial management, the quality of financial management and reporting and the productivity of MSMEs will increase.